Barriers for Access to New Medicines: Searching for the Balance Between Rising Costs and Limited Budgets - Godman, Brian; Bucsics, Anna; Vella Bonanno, Patricia; Oortwijn, Wija; Rothe, Celia C.; Ferrario, Alessandra; Bosselli, Simone; Hill, Andrew; Martin, Antony P.; Simoens, Steven; Kurdi, Amanj; Gad, Mohamed; et al. (Frontiers in Public Health, 2018)
Introduction: There is continued unmet medical need for new medicines across countries especially for cancer, immunological diseases, and orphan diseases. However, there are growing challenges with funding new medicines at ever increasing prices along with funding increased medicine volumes with the growth in both infectious diseases and non-communicable diseases across countries. This has resulted in the development of new models to better manage the entry of new medicines, new financial models being postulated to finance new medicines as well as strategies to improve prescribing efficiency. However, more needs to be done. Consequently, the primary aim of this paper is to consider potential ways to optimize the use of new medicines balancing rising costs with increasing budgetary pressures to stimulate debate especially from a payer perspective. Methods: A narrative review of pharmaceutical policies and implications, as well as possible developments, based on key publications and initiatives known to the co-authors principally from a health authority perspective. Results: A number of initiatives and approaches have been identified including new models to better manage the entry of new medicines based on three pillars (pre-, peri-, and post-launch activities). Within this, we see the growing role of horizon scanning activities starting up to 36 months before launch, managed entry agreements and post launch follow-up. It is also likely there will be greater scrutiny over the effectiveness and value of new cancer medicines given ever increasing prices. This could include establishing minimum effectiveness targets for premium pricing along with re-evaluating prices as more medicines for cancer lose their patent. There will also be a greater involvement of patients especially with orphan diseases. New initiatives could include a greater role of multicriteria decision analysis, as well as looking at the potential for de-linking research and development from commercial activities to enhance affordability. Conclusion: There are a number of ongoing activities across countries to try and fund new valued medicines whilst attaining or maintaining universal healthcare. Such activities will grow with increasing resource pressures and continued unmet need.